Kedudukan Pengungsi Taliban di Indonesia Ditinjau dari Asas Non-Refoulement - Brilianto, M. Andhika Fikri; Fikri, Anwar Hanifuddin; Hardianty, Ika Kurnia (JURNAL USM LAW REVIEW, 2022)
The purpose of this study is to describe the principle of Non-Refoulement, whether the application of the principle of Non-Refoulement is absolute or not, how urgent it is for Indonesia to apply the principle of Non-Refoulement, and how the position of Afghan refugees in Indonesia when viewed from the principle of Non-Refoulement and whether there are any sanctions obtained by Indonesia if it expels Afghan refugees from its territory. What is interesting to study is how the position of the Taliban refugees in Indonesia is viewed from the principle of Non-Refoulement, because the existence of these refugees is part of the law and the international community which indirectly involves Indonesia. The novelty of this research lies in the object studied, namely Afghan refugees and the principle of Non-Refoulement without involving other interdisciplinary legal aspects. The research method used is deductive qualitative. The results showed that the Non-Refoulement principle is a prohibition principle for expulsion of refugees, the application of the Non-Refoulement principle is not absolute based on article 33 paragraph 2 of the 1951 Convention, and Indonesia has no urgency to apply the Non-Refoulement principle. Furthermore, the position of Afghan refugees in Indonesia is as a transiting refugee and has rights in accordance with the 10 points of refugee position listed in the 1951 Convention, and no sanctions are applied if Indonesia does not accept the arrival of refugees to its country.Tujuan penelitian ini yaitu untuk mendeskripsikan prinsip Non-Refoulement, apakah penerapan prinsip Non-Refoulement itu mutlak atau tidak, bagaimana urgensi bagi Indonesia untuk menerapkan prinsip Non-Refoulement, dan bagaimana kedudukan pengungsi Afghanistan di Indonesia bila ditinjau dari prinsip Non-Refoulement serta apakah ada sanksi yang didapat oleh Indonesia jika mengusir pengungsi Afghanistan dari wilayahnya. Hal yang menarik untuk dikaji adalah bagaimana kedudukan pengungsi Taliban di Indonesia ditinjau dari asas Non-Refoulement, karena keberadaan pengungsi ini menjadi bagian dari hukum dan masyarakat internasional yang secara tidak langsung melibatkan Indonesia. Kebaharuan penelitian ini terletak pada objek yang dikaji yaitu pengungsi Afghanistan dan asas Non-Refoulement tanpa melibatkan aspek hukum interdisipliner lainnya. Metode penelitian yang digunakan adalah kualitatif. Hasil penelitian menunjukkan bahwa asas Non-Refoulement merupakan prinsip pelarangan untuk pengusiran pengungsi, penerapan asas Non-Refoulement tidak mutlak berdasarkan Pasal 33 ayat 2 Konvensi 1951, dan Indonesia tidak memiliki urgensi untuk menerapkan prinsip Non-Refoulement. Lebih lanjut, kedudukan pengungsi Afghanistan di Indonesia adalah sebagai pengungsi yang singgah dan memiliki hak-hak sesuai dengan 10 poin kedudukan pengungsi yang tercantum pada Konvensi 1951, serta tidak ada sanksi yang diterapkan apabila Indonesia tidak menerima kedatangan pengungsi ke negaranya.